PENGARUH NEGARA ASAL TERHADAP MINAT PEMBELIAN PRODUK KOSMETIK IMPOR DENGAN MODERASI VARIABEL PENGETAHUAN PRODUK - Lina Budiarti (Adbis: Jurnal Administrasi dan Bisnis, 2020)
This study aims to determine the effect of the country of origin on purchase intention of imported cosmetic products by moderating the variable product knowledge. The independent variables in this study are the country of origin, purchase intention as the dependent variable and product knowledge as the moderator variable. A total of 73 questionnaires were distributed to students in Malang that were selected using a purposive sampling technique, which was then analyzed using Partial Least Square (PLS) analysis. Purposive sampling technique is used to select students who use imported cosmetic products. All hypotheses in this study are accepted which showed that the country of origin influenced the purchase intention, and product knowledge moderated the influence of the country of origin on purchase intention.